Giant Ruptured Azygos Vein Aneurysm in a 33-Year-Old Woman - Uzdenov, Murat; Kroll, Johannes; Ballazhi, Fatos; Czerny, Martin (The Thoracic and Cardiovascular Surgeon Reports, 2023)
The rupture of an azygos vein aneurysm is a very rare but catastrophic complication. Careful differential diagnosis of acute dyspnea and thoracic pain in young patients is essential for effective and early management. We present the case of a young woman with a huge, spontaneously ruptured vena azygos saccular aneurysm, successfully repaired via median sternotomy under cardiopulmonary bypass.
Keywords: aneurysm; angiogenesis; imaging; venous disease